Application of Restorative Justice in Domestic Violence by Women's and Children Units of Barelang Resort Police - Retno Ariani (Airlangga Development Journal, 2020)
Domestic  violence  is  any  act  against  a  person  especially  a  woman,  resulting  misery  or physical,  sexual,  psychological  and  child  neglect  or  suffering.  Domestic  violence  is  a  hidden crime  because  there  are  many  victims,  but  few  report  incidents.  The  punishment  for  the perpetrators  must  be  considered  by  the  principle  of  expediency  and  justice.  If  the  concept  of restorative justice is done correctly, it can create justice and balance between the perpetrators of crime and the victims. The research method used in this paper is normative legal research, literature studies and case studies. The application of the concept of restorative justice carried out  by  women's  and  children  protection  units  of  the  Barelang  Resort  Police  is  making collaboration  with  CJS  and  related  agencies  such  as  social  services  in  handling  cases  of violence.  The  result  is  that  the  handling  of  domestic  violence  cases  in  the  Barelang  Resort Police can be more focused and resolved.